Childhood trauma and subclinical PTSD symptoms predict adverse effects and worse outcomes across two mindfulness-based programs for active depression - Nicholas K. Canby; Elizabeth A. Cosby; Roman Palitsky; Deanna M. Kaplan; Josie Lee; Golnoosh Mahdavi; Adrian A. Lopez; Roberta E. Goldman; Kristina Eichel; Jared R. Lindahl; Willoughby B. Britton (PLoS ONE, 2025)
Within mindfulness-based programs (MBPs), mixed results have been found for the role of childhood trauma as a moderator of depression outcomes. Furthermore, childhood trauma and PTSD symptoms have been identified as possible risk factors for the occurrence of meditation-related adverse effects (MRAE). The present research examined multiple forms of childhood trauma and PTSD symptoms as predictors of depression treatment outcomes and MRAEs. Various forms of childhood trauma (e.g., abuse and neglect) were examined as predictors of depression treatment outcomes and participant attrition using secondary analyses of two MBP clinical trials (N = 52 and 104, respectively). Study 2 also examined meditation-related side effects (MRSE) and MRAE as outcomes and current subclinical and past PTSD symptoms as predictors. Childhood trauma led to worse depression outcomes across both study 1 and study 2, such that total childhood trauma and childhood sexual abuse were significant predictors across both studies. Childhood sexual abuse predicted attrition in study 2. Finally, multiple forms of childhood trauma and PTSD symptoms predicted MRSE, while total childhood trauma, childhood emotional abuse, and subclinical PTSD symptoms predicted lasting MRAE. Childhood trauma and PTSD symptoms may lead to worse outcomes and a greater occurrence of adverse effects within MBPs for active depression. These results call for further trauma-sensitive modifications, safety monitoring, participant screening, and provider education when implementing these programs.